MODULATION OF ANGIOPOIETIN-LIKE 3 EXPRESSION - DOBIE, Kenneth; GRAHAM, Mark; CROOKE, Rosanne; LEE, Richard (2019)
Provided herein are methods, compounds, and compositions for reducing expression of an ANGPTL3 mRNA and protein in an animal. Also provided herein are methods, compounds, and compositions for reducing plasma lipids, plasma glucose and atherosclerotic plaques in an animal. Such methods, compounds, and compositions are useful to treat, prevent, delay, or ameliorate any one or more of cardiovascular disease or metabolic disease, or a symptom thereof.